2019
DOI: 10.7717/peerj.7592
|View full text |Cite
|
Sign up to set email alerts
|

Visual search characteristics of precise map reading by orienteers

Abstract: This article compares the differences in eye movements between orienteers of different skill levels on map information searches and explores the visual search patterns of orienteers during precise map reading so as to explore the cognitive characteristics of orienteers’ visual search. We recruited 44 orienteers at different skill levels (experts, advanced beginners, and novices), and recorded their behavioral responses and eye movement data when reading maps of different complexities. We found that the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
1
Order By: Relevance
“…Compared with other sports, orienteers have certain cognitive advantages in spatial cognition [ 33 ]. Specific cognitive training in orienteering enables orienteering practitioners to master effective visual search strategies [ 34 ]. A study by Eccles found that those who were good at using attention and spatial memory during orienteering route-planning could complete the race effectively [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other sports, orienteers have certain cognitive advantages in spatial cognition [ 33 ]. Specific cognitive training in orienteering enables orienteering practitioners to master effective visual search strategies [ 34 ]. A study by Eccles found that those who were good at using attention and spatial memory during orienteering route-planning could complete the race effectively [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Örneğin, karmaşık ve efektif olmayan bir harita, aşırı derece ilgi çekici görsel bir unsur olmadığı varsayıldığında, katılımcılarda daha uzun sabitleme sürelerine neden olacaktır. Sabitleme sıklığı ya da birim zamandaki sabitleme sayısı, gerçekleştirilen görevin işlem hızı hakkında bilgi vermektedir ve harita kullanıcısı ne denli bilgi ve beceri sahibiyse, haritadan bilgi çıkarımı o denli yüksek olacak, bir başka deyişle, birim zamana düşen bilgi edinimi o oranda artacaktır (Liu, 2019). Bu çalışmada bilişsel yük değerlendirmesi için saniyedeki ortalama sabitleme sayısı ve ortalama sabitleme süresi metrikleri kullanılmıştır (Togami, 1984;Gedminas, 2011;Ooms, 2012).…”
Section: Deney Iunclassified
“…As a type of memory, spatial memory is the storage and processing of spatial information [ 6 ]. Currently, studies on the cognitive abilities of orienteers have confirmed that orienteers have good map-recognition memory [ 7 ], and memory ability is highly correlated with athlete level, as in the study by Lunze, who found that the map-recognition ability of German national orienteering team athletes was higher than that of ordinary university students, and that the better spatial memory ability of professional athletes comes from years of sports experience and expertise training [ 8 ]. However, further research is needed to clarify whether this memory advantage of high-level orienteers is innately developed or acquired through later training.…”
Section: Introductionmentioning
confidence: 99%